URGENSI ATTACHMENT PADA PERKEMBANGAN PSIKOLOGIS ANAK: SUATU TINJAUAN PSIKOLOGI PERKEMBANGAN - Fatimah, Sitti (Institut Agama Islam Negeri Bone, 2019)
Attachment is an emotional connection to a figure that causes a child to look for the figure's presence and expect affection so that the child will feel safe. This attachment shows the affective relationship that will last a long time in a person's life span. The development of attechment in a child has four stages. But the development varies greatly from child to child, because it is greatly influenced by the child's condition and the environment in which the child lives and is raised. Attachment is really needed by every child considering sticky behavior is very supportive of their development. To parents, it is better to pay attention to the psychological needs of these children by realizing that the presence of an adult as a stick figure for a child is a basic need for a child. Especially to a mother, who is the most expected figure of a child to become aÂ figure to attach.Keywords: Attachment, A child, Psychological Development